The bile acid activated receptors GPBAR1 and FXR exert antagonistic effects on autophagy. Issue 1 (24th December 2020) - Carino, Adriana; Marchianò, Silvia; Biagioli, Michele; Scarpelli, Paolo; Bordoni, Martina; Di Giorgio, Cristina; Roselli, Rosalinda; Fiorucci, Chiara; Monti, Maria Chiara; Distrutti, Eleonora; Zampella, Angela; Fiorucci, Stefano
Abstract: Autophagy is a highly conserved catabolic process activated by fasting and caloric restriction. FXR, a receptor for primary bile acids, reverses the activity of cAMP‐response element binding protein (CREB) on autophagy‐related genes (Atg)s and terminates autophagy in the fed state. GPBAR1, a receptor for secondary bile acids, exerts its genomic effects via cAMP‐CREB pathway. By genetic and pharmacological approaches, we have obtained evidence that GPBAR1 functions as a positive modulator of autophagy in liver and white adipose tissue (WAT) in fasting. Mechanistically, we found that Gpbar1 −/− mice lack the expression of Cyp2c70 a gene essential for generation of muricholic acids which are FXR antagonists, and have an FXR‐biased bile acid pool. Because FXR represses autophagy, Gpbar1 −/− mice show a defective regulation of autophagy in fasting. BAR501, a selective GPBAR1 agonist, induces autophagy in fed mice. Defective regulation of autophagy in Gpbar1 −/− could be reversed by FXR antagonism, while repression of autophagy by feeding was partially abrogated by FXR gene ablation, and FXR activation repressed Atgs in the fast state. BAR501 reversed the negative regulatory effects of feeding and FXR agonism on autophagy and promoted the recruitment of CREB to a CRE on the LC3 promoter. In mice exposed to chronic high caloric intake, GPBAR1 agonism ameliorated insulin sensitivity and induced Atgs expression in the liver and WAT. In summary, GPBAR1 is required for positive regulation of autophagy in fasting and its ligands reverse the repressive effects exerted on liver and WAT autophagy flow by FXR in fed.